Bibliometric Analysis of the Effects of Prolonged Preoperative Fasting on Patients - Rahman, Taupik; Arifin, Syamsul; Lahdimawan, Ardik; Noor, Meitria Syahadatina; Illiandri, Abdullah Oski; Suhartono, Eko (Universitas Malahayati, 2025)
ABSTRACT Preoperative fasting is a common practice in the surgical field, which aims to minimize complications and ensure patient safety. Understanding its impact and optimizing protocols are essential in clinical practice. This study analyzed the bibliometric and network overview of publications on the effects of extended preoperative fasting on patients, using VOSViewer. This bibliometric analysis explores the research landscape on the effects of extended preoperative fasting duration on patients. Using VOSViewer, this study identified key contributors and clusters in the literature, highlighting significant research gaps. Bibliometric methods were used to analyze publications regarding the effects of extended preoperative fasting. Using VOSViewer, this study identified key contributors and groups in the literature, which highlighted significant research gaps. Bibliometric methods were used to analyze publications regarding the effects of extended preoperative fasting. Data were aggregated and visualized using VOSViewer to map the publication network and identify thematic clusters. China and the UK emerged as the main contributors with 7 articles each, followed by Brazil and India. Three main clusters were identified: a red cluster focusing on fasting duration, side effects, dehydration risk, and intraoperative management; a blue cluster exploring the effects of fasting on surgical outcomes, hunger, and procedural aspects; and a green cluster addressing guideline development, elective surgery, and preoperative preparation. These findings underscore the importance of extended preoperative fasting in clinical practice and highlight significant research opportunities. Future research could focus on personalized fasting protocols, long-term effects, psychological impact, and innovative monitoring technologies to improve the quality of patient care. Keywords: Preoperative Fasting, Effects Of Prolonged Fasting, Bibliometric Analysis, Vosviewer, Surgical Outcomes, Patient Care